Presencia en Guadalupe de Aphelenchoides besseyi Christie1942 (Nematoda, Aphelenchoididae) en follaje del mapuey: Dioscorea trifida L. - Kermarrec, A.; Anais, A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Aphelenchoides bessyi has been found in foliage and tubers of yam (Dioscorea trifida) in Guadalupe. It´s morphological data are compared to those of the American and African races. A hosts review and a geographical distrivbution are established